Distribution of Dopamine Receptor 2 DRD2 rs1800497 Polymorphisms in Professional Football Players - Beste Tacal Aslan; Özlem Özge Yılmaz; Tolga Polat; Çisem Şılar; Başak Funda Eken; Canan Sercan Doğan; Korkut Ulucan (Türk Spor ve Egzersiz Dergisi)
According to the literature, the genetic makeup of athletes contributes to their athletic performance. Athletic performance depends on genetic and environmental factors relating to the athlete. The study of sports genetics includes extensive research into identifying genes that affect athletic performance. Psychological factors affect athletic performance and so dopamine contributes to the determination of that performance. One of the neurotransmitters of the dopaminergic system is dopamine, which affects the athlete mentally and psychologically. The dopamine receptor D2 (DRD2) rs1800497 polymorphism affects the brain’s dopaminergic system and athletic performance. This study aimed to determine the genotype and allele distributions of the DRD2 rs180047 polymorphism in football players and compare them with the control group. For this purpose, 21 football players were enrolled in our study. Genotyping was performed by PCR after DNAs were isolated from buccal epithelial cells. When we examined the genotype distributions, the AG and GG were found as 5 (24%) and 16 (76%), respectively. No AA genotype was found for DRD2. When allelic distributions were examined in the athlete group, the A allele was counted as 5 (12%) and the G allele as 37 (88%). In our study cohort, the DRD2 rs1800497 polymorphism was found to be dominated by the GG genotype and the G allele. We believe that the DRD2 A allele is associated with addiction and thus with athletic performance. However, more studies with athletes from different branches are needed to reveal the effect of DRD2 rs1800497 polymorphism on athletic performance.